GENERATION OF PLATE TECTONICS FROM LITHOSPHERE-MANTLE FLOW AND VOID-VOLATILE SELF-LUBRICATION - Bercovici D. (My University, 1998)
The formation of plate tectonics from mantle convection necessarily requires nonlinear rheological behavior. Recent studies suggest that self-lubricating rheological mechanisms are most capable of generating plate-like motion out of fluid flows. The basic paradigm of self-lubrication is nominally derived from the feedback between viscous heating and temperature-dependent viscosity. Here, we propose a new idealized self-lubrication mechanism based on void (e.g., pore and/or microcrack) generation and volatile (e.g., water) ingestion. We test this void-volatile self-lubrication mechanism in a source-sink flow model; this leads to a basic nonlinear system which permits the excitation of strike-slip (toroidal) motion (a necessary ingredient of plate-like motion) out of purely divergent (i.e., poloidal or characteristically convective) flow. With relatively inviscid void-filling volatiles, the void-volatile mechanism yields a state of highly plate-like motion (i.e., with uniformly strong plate interiors, weak margins, and extremely focussed strike-slip shear zones). Moreover, the void-volatile model obeys a chemical diffusion time scale that is typically much longer than the thermal convection time scale; the model thus complies with the observation that plate boundaries are long lived and survive even while inactive. The void-volatile model of self-lubrication therefore predicts self-focussing shear zones, plate generation, and plate-boundary longevity through what has long been suspected to be a key ingredient for the existence of plate tectonics, i.e., water.
Keywords: PLATE TECTONICS; PLATES; MANTLE; CONVECTION; VISCOSITY; STRIKE-SLIP FAULTS